Al-doping enables high stability of single-crystalline LiNi0.7Co0.1Mn0.2O2 lithium-ion cathodes at high voltage. Issue 1 (22nd December 2020) - Cheng, Lei; Zhang, Bao; Su, Shi-Lin; Ming, Lei; Zhao, Yi; Tan, Xin-Xin
Abstract : In this work, the single-crystalline LiNi0.7 Co0.1 Mn0.2 O2 materials with stable and ordered crystal structure have been synthesized by Al-doping, which display the advanced Li + -ion storage property. Abstract : LiNi0.7 Co0.1 Mn0.2 O2 (NCM) is a kind of promising cathode material for lithium ion batteries because of its high capacities. However, the further commercialization of this material has been seriously hindered by the unstable structure at a deep de-lithiation state. Herein, it is identified that this drawback can be diminished by Al-doping, which is inherently stable in the lattice framework to restrain the structural collapse of LiNi0.7 Co0.1 Mn0.2 O2 at a high cut-off voltage (4.4 V). As expected, the Al-doped NCM (NCM–0.2Al) material obtains the highest reversible capacity and capacity retention (144.69 mA h g −1, 80.26%) after 90 cycles at 1C. The excellent performance demonstrates that Al-doping can effectively enhance the Li + -ion diffusion kinetic and structural stability of NCM, providing a feasible strategy for the further industrialization of Ni-rich materials.